2018
DOI: 10.1007/s13201-018-0801-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of Vaitarna and Ulhas river basins, Maharashtra, India: using geospatial techniques

Abstract: Drainage network quantification with respect to the climate, tectonics, lithology and geomorphology provides significant evidence of the drainage development, hydro-geomorphic and denudation characteristics of an area. The present study was carried out by using Shuttle Radar Topographic Mission DEM to study the drainage morphometry and its influence on the hydrological characteristics of Vaitarna and Ulhas basins in Maharashtra, India. Results of the morphometric analysis reveal that the catchment of Vaitarna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The rotation ought to be such that getting important physical information from the subsequent components are possible. Thus, using Equations (1) and (12) and expression H = C −1 R, the original PCs can be composed as:…”
Section: Principal Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The rotation ought to be such that getting important physical information from the subsequent components are possible. Thus, using Equations (1) and (12) and expression H = C −1 R, the original PCs can be composed as:…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Over recent years various researchers have used morphometric variables (i.e., linear, areal, and shape) to prioritize watersheds using the application of remote sensing (RS) and geographical information system (GIS) by ordinary methods [4][5][6][7][8][9][10][11][12][13]. For instance, Shrimali et al [4] applied the feasibility of RS and GIS techniques to contextually investigate the Sukhana lake catchment in the Shiwalik hills to prioritize the soil erosion zones.…”
Section: Introductionmentioning
confidence: 99%
“…Richard and Pike (2000), Bardossy and Schmidt (2002), Grohmann (2004), Marchi and Fontana (2005), Kouli et al (2007), Esper (2008, Hlaing et al (2008), Akar (2009), Ajibade et al (2010 and Thomas et al (2010) used remote sensing and GIS techniques for drainage morphometry analysis. Das and Pardeshi (2018) worked on the morphometric analysis of Vaitarna and Ulhas river basins in Maharashtra. Radwan et al 2017 andMalik andShukla (2018) reported on the analysis, respectively, in the Wadi Baish dam catchment area and Kandaihimmat watershed in Madhya Pradesh using GIS-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…Shuttle Radar Topographic Mission (SRTM) derived Digital Elevation Model (DEM) of 3 arc-second (90 m) data was acquired from CGIAR official portal (http://srtm.csi.cgiar.org/). SRTM data has been preferred in this study because of its higher vertical accuracy (Forkuor and Maathuis 2012;Sun et al 2003;Das and Pardeshi 2018). The average annual rainfall data were obtained from the worldclim data hub (https://www.worldclim.org/).…”
Section: Methodsmentioning
confidence: 99%
“…Several factors such as lithology, tectonic, and climate shape the landscape and drainage network (Das and Pardeshi 2018). To understand the dominant role of factors in such geomorphic control, it is essential to establish relationship between the morphometric variables with measured climate, hydrology, and erosion rate data.…”
mentioning
confidence: 99%